GAMBARAN SIKLUS MENSTRUASIPADA REMAJA OBESITAS DI SMAN 6 KOTA PEMATANGSIANTAR - Sukaisi, Sukaisi (JURNAL HEALTH REPRODUCTIVE, 2020)
Background: The prevalence of obesity has increased significantly in the world, including the prevalence of obesity in Indonesia. Obesity in adolescents is at risk of metabolic syndrome disease. Obesity in women related to menstrual disorders and decreased fertility in adolescence and group years. Methods: This study is a descriptive study with the aim of obtaining an overview of the menstrual cycle in adolescents. This study was conducted on 52 obese adolescents with a BMI> 30 in grade 12 at SMAN6, aged 17-18 years, who were healthy and had no history of disease and drug consumption. Measurement of the menstrual cycle using a questionnaire, categorized as regular and irregular. Results: Obtained from 52 obese adolescents with abnormal menstrual cycles 32 people (61.5%). Conclusion: the term obese adolescent is characterized by irregular menstrual cycles. There needs to be continued research related to menstrual cycle fluctuations with normal BMI